The The Development of the Life Insurance Market in Central and Eastern European Countries - Laskowska, Iwona (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The need to implement the process of economic transformation in the recent past is what significantly differentiates the countries of Central and Eastern Europe from other members of the European Union. Integration into the financial system of the European Union has been an important factor influencing the process of transformation of the life insurance sector and the establishment of the level of competition, as well as the quality and scope of insurance services offered. In addition, the improvement in the macroeconomic situation and the increase in household income have had a significant impact on the growth in demand for insurance products from the life insurance segment. Despite positive changes, the insurance market of Central and Eastern European countries remains a relatively underdeveloped market, and its structure, unlike that of Western European countries, is dominated by property insurance. This points towards a need for further research into the determinants of life insurance market growth in this region of Europe. Aim: The aim of this paper is twofold. The first part presents an assessment of the level of development of the life insurance market in ten countries of Central and Eastern Europe over the period 2011-2021 using the method of multivariate comparative analysis in dynamic terms. The second part of the paper is devoted to an attempt to identify the determinants of the development of this market using econometric models for panel data. Results: The life insurance market varies widely among the group of countries considered. The trends of change during the period under consideration were also different. The most severe downturn in the life insurance market was recorded in Poland and the Czech Republic. Significant development was observed in Lithuania and Latvia, countries with an underdeveloped market in the past. The econometric models used confirmed the impact of economic development on the life insurance market.